2018
DOI: 10.1111/den.13036
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of traction‐assisted colorectal endoscopic submucosal dissection using a clip‐and‐thread technique: A prospective randomized study

Abstract: Traction-assisted colorectal endoscopic submucosal dissection reduced the procedure time and increased the self-completion rate by the intermediates (UMIN000018612).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 34 publications
2
89
0
3
Order By: Relevance
“…It was reported that the method of traction assisted ESD made colorectal ESD easier and safer. 1 There are various methods for making a traction. [1][2][3][4][5] The method of using a clip with ring-thread is cost-efficient, in addition, we can use the prepared various sizes of the ring-threads for various situations.…”
Section: E Ndoscopic Submucosal Dissection (Esd)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the method of traction assisted ESD made colorectal ESD easier and safer. 1 There are various methods for making a traction. [1][2][3][4][5] The method of using a clip with ring-thread is cost-efficient, in addition, we can use the prepared various sizes of the ring-threads for various situations.…”
Section: E Ndoscopic Submucosal Dissection (Esd)mentioning
confidence: 99%
“…1 There are various methods for making a traction. [1][2][3][4][5] The method of using a clip with ring-thread is cost-efficient, in addition, we can use the prepared various sizes of the ring-threads for various situations. The easiest method of attaching the ringthread to the clip is passing one side of the ring-thread through the crossing part of the clip arm (Video S1); however, sometimes the ring-thread drops off from the clip.…”
Section: E Ndoscopic Submucosal Dissection (Esd)mentioning
confidence: 99%
“…The S‐O clip (Zeon Medical, Tokyo, Japan) is a marketed traction device without a thread, consisting of a clip and spring for ESD, compared with the clip‐with‐thread method (Fig. b) . It can pull a lesion upward and facilitates speedy submucosal dissection.…”
Section: Brief Explanationmentioning
confidence: 99%
“…36,37 A recent RCT compared conventional ESD with Traction ESD using a clip and thread. 38 In this procedure, a surgical thread is tied to the end of a clip, the combination of which is used to grasp the specimen and lift it, allowing good visualization of the dissection plane. Traction ESD demonstrated an ESD time of 40 min compared to 70 min for conventional ESD.…”
Section: Futuristic Lookmentioning
confidence: 99%